ANALYSIS OF THE BENEFITS AND CHALLENGES IN ATTRACTING FOREIGN INVESTMENT TO THE REPUBLIC OF UZBEKISTAN - Sultabaeva Munira Bahodirovna; Pulatova Mokhira Bakhtiyorovna (Journals Park Publishing, 2023)
Attracting foreign investment is one of the most important aspects influencing the country's economic progress. There is an issue of insufficient attracted foreign investment in the Republic of Uzbekistan, as well as in other nations. This article examines the benefits and drawbacks of bringing foreign investment to Uzbekistan.
Keywords: investment, business, finance, industry, export, company, technology, risk, production.